ChemInform Abstract: A Versatile and Highly Efficient Method for 1‐Chlorination of Terminal and Trialkylsilyl‐Protected Alkynes. Issue 33 (19th August 2014) - Gulia, Nurbey; Pigulski, Bartlomiej; Charewicz, Marta; Szafert, Slawomir
Abstract An efficient procedure for the chlorination of trialkylsilyl‐substituted alkynes is developed.